ANALYSIS OF STUDENTS' DIFFICULTY IN SOLVING MATHEMATICS STORY PROBLEMS IN NUMBER PATTERN MATERIALS - Yulius Yusman Laia (Universitas Nias Raya, 2022)
This study aims to analyze the form of difficulties, the causes of students' difficulties in solving problems, and the ways that can be done to overcome student difficulties. This type of research is a qualitative research with a descriptive approach. The informants in this study were class VIII-C students of SMP Negeri 1 Luahagundre Maniamolo. Data were analyzed by using data reduction, data presentation, and conclusion drawing, as well as fishbone analysis. This research data collection technique is through tests and interviews. The results showed that: (1) students were unable to identify elements that were known and asked in the questions, used the wrong formulas, were unable to use predetermined formulas and made mistakes in substituting the known element values ​​in the questions, and concluded that the answers were not in accordance with the context of the questions, (2) students' difficulties in solving word problems on number pattern material caused by: lack of interest in student learning, low students' mathematical problem solving abilities, teachers do not attend class, how to teach teachers too quickly, ways of educating children by parents are less assertive , low parental economics, friends around who attract students' attention to play, and misuse of technology.